Identification and characterization of a novel Epstein-barr virus-encoded circular RNA from LMP-2 Gene / Tan Ke En - Tan , Ke En (2022)
Epstein-Barr virus (EBV) is a common human herpesvirus that establishes lifelong infection in its hosts and accounts for various malignancies. EBV was recently found to encode novel circular RNAs (circRNAs) through backsplicing. However, the cataloguing, characterization and functional study of EBV circRNAs are still lacking. Utilizing computational algorithms, psirc and find_circ, a list of putative EBV circRNAs in GM12878, an EBV-transformed lymphoblastoid cell line, was identified with a significant majority encoded from the EBV latent genes. A novel EBV circRNA derived from the exon 5 of LMP-2 gene (termed as circLMP-2_e5) with the highest read count was further validated by RNase R assay and Sanger sequencing. Characterization of circLMP-2_e5 demonstrated that it was readily detected in a panel of EBV-positive cell lines modelling different latency programs, ranging from lower expression in NPC cells to higher expression in B cells and was localized to both cytoplasm and nucleus. Subsequent experiments showed that circLMP-2_e5 was expressed concomitantly with the linear LMP-2 upon EBV lytic reactivation and may be produced as a result of exon skipping with its circularization possibly occur without the presence of cis elements in the short flanking introns. Furthermore, functional characterization showed that circLMP-2_e5 was unlikely to act as a microRNA sponge, and did not affect cell proliferation, host innate immune response, LMP-2 linear transcripts and EBV lytic reactivation. Taken together, this study does not only provide informative addition to the current repertoire of putative EBV circRNAs, but also deepen our understanding of EBV circRNA biology. The results have also laid essential foundation for further investigations on the functional significance of circLMP-2_e5 in EBV life cycle and the development of EBV-associated diseases.